MONITORING SISTEM DC 110 VOLT DI GARDU INDUK BERBASIS ANDROID - Nurholis; Tamaji (Universitas Widya Kartika Surabaya, 2024)
The 110 Volt DC system is a critical component in substations that supports the operation of control and protection devices. Instability in voltage or current within this system can have severe consequences on the overall performance of the substation. Therefore, real-time monitoring of the 110 Volt DC system is crucial. This research aims to design and implement an Android-based monitoring system supported by Internet of Things (IoT) technology. The system utilizes voltage and current sensors integrated with a microcontroller, transmitting data to an Android application via a data communication protocol. The data received by the application can be analyzed in real-time, providing essential information about parameter deviations fromoperational standards. Additionally, the system includes an early warning feature that enables technicians to respond to potential issues before they affect the substation’s operations. Testing has demonstrated that this system effectively improves monitoring efficiency and reduces operational risks in substations. By applying this technology, disruptions in the DC system can be detected early, allowing for rapid and accurate preventive action.